Determination of Router Location for Optimizing Computer Network Using Dominating Set Methods - Nova El Maidah; Ivan Hardja; Slamin Slamin (IAES Indonesia Section, 2018)
The aims of this research is to develop a system to determine an optimal router location in a computer network. The router location is optimal if the computer network need the minimal number of router without losing the network connectivity. The methods used in order to optimize the router location are dominating set and Greedy algorithm. The data is the router location of computer network in University of Jember. The result showed that the optimal router needed in the networks is 4. These routers were found by using the determination system that implement Greedy algorithm to find the minimum number of dominating set.